2021
DOI: 10.3390/ijerph18073399
|View full text |Cite
|
Sign up to set email alerts
|

Instrument Development and Validation to Assess Care Barriers for Patients in Saudi Arabia with Oral Clefts

Abstract: The study objective was to construct and validate a tool to assess, measure, and evaluate the barriers and obstacles that patients with orofacial clefts (OFCs), and their families, face during treatment. The Effective Accessibility and Accommodation subscale, based on the translated Primary Care Assessment Survey and Primary Care Assessment Tool scales, was used as a reference for the questionnaire. A total of 165 parents from three main cleft referral centers in Saudi Arabia were interviewed. Questionnaire co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…There were 3 factors (geographic accessibility, appointment availability and accessibility, and scheduling-related barriers) with eigenvalues above 1.00, which collectively accounted for 73% of the variance. Hence, this tool is valid and reliable for evaluating the accessibility to and barriers for patients requiring OFC care in Saudi Arabia (Khogeer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 3 factors (geographic accessibility, appointment availability and accessibility, and scheduling-related barriers) with eigenvalues above 1.00, which collectively accounted for 73% of the variance. Hence, this tool is valid and reliable for evaluating the accessibility to and barriers for patients requiring OFC care in Saudi Arabia (Khogeer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Internal consistency for the 9-item Arabic version was verified in a sample of 19 parents of children with OFC. Cronbach a was calculated for the 9-item Arabic version, and the result revealed that the questionnaire was reliable (Cronbach a ¼ .86; Khogeer et al, 2021).…”
Section: Assessment Of the Study Questionnairementioning
confidence: 99%